Jornada imaginativa: o problema da experiência transmissiva e cultural na perspectiva de Giorgio Agamben - Jungblut, Ana Carolina (2010)
Under Giorgio Agamben s perspective we search for the theoretical foundations which have involved the imagination during the western history until the moment in that this history is expropriated of the knowledge. We take into account what imagination notion is inserted in a context of cultural transmission which each time generates for the next one and, however, also modifies their foundations. We understand the imagination since the concept of phantasm, in other words, it is not an isolated term, but it is involved in a cultural complexity and interlaced of characteristics which are connected to memory, dream, language, desire, melancholy and sensation and define the great imaginative particularity of ghost which is immaterial, abstract and still related to the character of spirit. In the first part we develop the theory of Aristotle s ghost that has its first links to the old theory of pneuma starting from stoicism and mainly neoplatonism. From this union it was obtained the notion of fantastic spirit that influence the medieval period intensely. In this culture we know important facts that lead us to understand the mechanisms of imagination as well as the subtle first aspects of the expropriation process of imagination in western culture. Plus than everything the ontological reformulation that happens in the modernity generates an expropriation of the experience subject (psyché), correlated phenomenon to the expropriation of the imagination, generating an insert in the conflict between rational and irrational. In the second part we approach firstly the effects of the exclusion of imagination before the transmissive experience, in other words, the traditional and narrative experience which opposes to the scientific experiment. This is, so we could say, in a mythological level, in the sense of the use of the words while they make us sense for life. Secondly we approach an experience that interferes in what we could name, ritualistic, in the sense of the invasion of the creations and of the doing of culture of the subjects in society. However, how it seems, these two inaccessible spheres in the current days await new possibilities for being demarcated. According to Agamben, these activities are never abandoned as fantasmatic practices by the adult, although we are losing this potentiality nowadays and, in this way, t heir consequences in the destruction of the experience, and in the impossibility to use this potentiality, are just reflexes of the destruction of history and the cultural dominance. Agamben notices that the symbolic forms, the textual practices, the creations of human culture, all need to take the negative, in other words, the absent object (phantasm) to shape certain reality. The experience seems to have a sense not exactly in the concrete sphere, but among the imaginative sphere and like this, it strongly demarcates the limitations that the western culture ended up leaving in second plan. In the case of the linguistic manifestation, we have the resistant sign to all significance represented by the metaphor. In the case of the using or of the doing of human being, which far away from demarcating its usefulness strays for the absence of the object fetish. To capture these limitations and their exits through the linguistic theory of Childhood and through the theory of the game of Profanation are the proposals of Agamben.